2014
DOI: 10.1159/000358595
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Placental Growth Factor Isoforms 1 and 2 at 11-13, 20-24 and 30-34 Weeks' Gestation in Late-Onset Pre-Eclampsia and Small for Gestational Age Neonates

Abstract: Objective: To compare the maternal serum concentrations of placental growth factor (PlGF)-1 and PlGF-2 in the first, second and third trimesters in normal pregnancies and in those complicated by pre-eclampsia (PE) or the delivery of small for gestational age (SGA) neonates after 37 weeks. Methods: Serum PlGF-1 and PlGF-2 were measured at 11-13, 20-24 and 30-34 weeks' gestation in 50 cases of PE, 99 cases of SGA and 298 controls. The values of PlGF-1 and PlGF-2 at 11-13 weeks were expressed as multiples of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Reports on the capability of PlGF to predict SGA have been conflicting. Initial small case–control studies in the first and second trimesters for the prediction of SGA found no significant relationship, but subsequent larger case–control studies and several prospective cohorts measuring PlGF in the second and first trimesters have reported an association between low PlGF concentrations and early‐onset pre‐eclampsia, stillbirth and SGA. The few small ( n = 21 or fewer), mainly case–control studies in which measurement was undertaken in the third trimester (including at time of delivery), generally concur with our finding of low PlGF concentration in women with subsequent delivery of a SGA infant, particularly those with significant underlying placental pathology.…”
Section: Discussionsupporting
confidence: 80%
“…Reports on the capability of PlGF to predict SGA have been conflicting. Initial small case–control studies in the first and second trimesters for the prediction of SGA found no significant relationship, but subsequent larger case–control studies and several prospective cohorts measuring PlGF in the second and first trimesters have reported an association between low PlGF concentrations and early‐onset pre‐eclampsia, stillbirth and SGA. The few small ( n = 21 or fewer), mainly case–control studies in which measurement was undertaken in the third trimester (including at time of delivery), generally concur with our finding of low PlGF concentration in women with subsequent delivery of a SGA infant, particularly those with significant underlying placental pathology.…”
Section: Discussionsupporting
confidence: 80%
“…While there are few studies focused on circulating levels of the different PlGF isoforms, maternal levels of serum PlGF‐1 and PlGF‐2 are highly correlated. That is, both increase with gestational age and have similar predictive value for late preeclampsia and delivery of small for gestational age offspring . Similarly, in conditions characterized by aberrant expression of PlGF, such as rheumatoid arthritis, both the PlGF‐1 and PlGF‐2 isoforms increased survival, migration, and invasiveness of rheumatoid fibroblast‐like synoviocytes, although differences in PlGF‐1 and PlGF‐2 expression have been described in the setting of malignancy (eg, breast cancer) …”
Section: Discussionmentioning
confidence: 99%
“…Differences between assay results may in part be due to different degrees of cross-reactivity between PlGF-1 and alternative isoforms, which may have varying degrees of sensitivity for preeclampsia; however, this is unlikely to be a major factor in late pregnancy. 32,33 The higher sensitivity could be helpful when wanting to identify as many women with preeclampsia as possible. Yet a large number of false positives would need extra clinical attention to exclude the diagnosis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%